A cada uno según sus fuerzas: the circulation of anarchist forms in the formation of the workers' movement in Buenos Aires (1890-1905) - Cunha, Eduardo Augusto Souza (Universidade de São Paulo | Escola de Comunicações e Artes, 2019)
The present study aims to approach the circulation of anarchist newspapers, books and leaflets during the period of formation of workers' organizations in Buenos Aires. In our investigation, we conclude that the anarchist publishing circuit had a particular brand when compared to the production and circulation of printed matter in the emerging publishing market in Buenos Aires. In an attempt not to commercialize their publications, the anarchists used a voluntarist conception that both made possible a meaningful distribution and brought instability to editorial projects over the years. Thus, we believe that the analysis of the production and circulation of the anarchist printed matter in Buenos Aires can be considered an example of an editorial production of the subaltern classes.